Adipose Extracellular Vesicles: Messengers From and to Macrophages in Regulating Immunometabolic Homeostasis or Disorders - Zhou, Zixin; Tao, Yan; Zhao, Hui; Wang, Qun (Frontiers in Immunology, 2021)
Adipose tissue is comprised of heterogenous cell populations that regulate both energy metabolism and immune reactions. Macrophages play critical roles in regulating immunometabolic homeostasis or disorders through cooperation with adipocytes, adipose tissue-derived stem cells (ADSCs) or other cells in adipose tissue. Extracellular vesicles (EVs) are recently recognized as efficient messengers for intercellular communication. Emerging evidences have demonstrated that adipose EVs are actively involved in the mutual interactions of macrophages, adipocytes and ADSCs, which produce considerable influences on immunometabolism under healthy or obese conditions. Here, we will elaborate the production and the characteristics of adipose EVs that are related to macrophages under different metabolic demands or stresses, whilst discuss the roles of these EVs in regulating local or systemic immunometabolic homeostasis or disorders in the context of adipocyte-macrophage dialogue and ADSC-macrophage interaction. Particularly, we provide a profile of dynamic adipose microenvironments based on macrophages. Adipose EVs act as the messengers between ADSCs and macrophages to maintain the balance of metabolism and immunity, while drive a vicious cycle between hypertrophic adipocytes and inflammatory macrophages to cause immunometabolic imbalance. This review may provide valuable information about the physio- or pathological roles of adipose EVs and the application of adipose EVs in the diagnosis and treatment of metabolic diseases.